Accelerated stenotic flow in the left anterior descending coronary artery explains the causes of impaired coronary flow reserve: an integrated transthoracic enhanced Doppler study - Caiati, Carlo; Pollice, Paolo; Iacovelli, Fortunato; Sturdà, Francesca; Lepera, Mario Erminio (Frontiers in Cardiovascular Medicine, 2023)
Background Accelerated stenotic flow (AsF) in the entire left anterior descending coronary artery (LAD), assessed by transthoracic enhanced color Doppler (E-Doppler TTE), can reveal coronary stenosis (CS) and its severity, enabling a distinction between the microcirculatory and epicardial causes of coronary flow reserve (CFR) impairment. Methods Eighty-four consecutive patients with a CFR <2.0 (1.5 ± 0.4), as assessed by E-Doppler TTE, scheduled for coronary angiography (CA) and eventually intracoronary ultrasounds (IVUS), were studied. CFR was calculated by the ratio of peak diastolic flow velocities: during i.v. adenosine (140 mcg/Kg/m) over resting; AsF was calculated as the percentage increase of localized maximal velocity in relation to a reference velocity. Results CA showed ≥50% lumen diameter narrowing of the LAD (critical CS) in 68% of patients (57/84) vs. non-critical CS in 32% (27/84). Based on the established CA/IVUS criteria, the non-critical CS subgroup was further subdivided into 2 groups: subcritical/diffuse [16/27 pts (57%)] and no atherosclerosis [11/27 pts (43%)]. CFR was similar in the three groups: 1.4 ± 0.3 in critical CS, 1.5 ± 0.4 in subcritical/diffuse CS, and 1.6 ± 0.4 in no atherosclerosis (p = ns). Overall, at least one segment of accelerated stenotic flow in the LAD was found in 73 patients (87%), while in 11 (13%) it was not. The AsF was very predictive of coronary segmental narrowing in both angio subgroups of atherosclerosis but as expected with the usage of different cutoffs. On the basis of the ROC curve, the optimal cutoff was 109% and 16% AsF % increment to successfully distinguish critical from non-critical CS (area under the curve [AUC] = 0.99, p < 0.001) and diffuse/subcritical from no CS (AUC = 0.91%, p < 0.001). Sensitivity and specificity were 96% and 100% and 82% and 100%, respectively. Conclusion E-Doppler TTE is highly feasible and reliable in detecting the CS of any grade of severity, distinguishing epicardial athero from microvascular causes of a severe CFR reduction.